2023
DOI: 10.1002/smll.202206232
|View full text |Cite
|
Sign up to set email alerts
|

Oligomer Dynamics of LL‐37 Truncated Fragments Probed by α‐Hemolysin Pore and Molecular Simulations

Chang Liu,
Anja Henning‐Knechtel,
Nicklas Österlund
et al.

Abstract: Oligomerization of antimicrobial peptides (AMPs) is critical in their effects on pathogens. LL‐37 and its truncated fragments are widely investigated regarding their structures, antimicrobial activities, and application, such as developing new antibiotics. Due to the small size and weak intermolecular interactions of LL‐37 fragments, it is still elusive to establish the relationship between oligomeric states and antimicrobial activities. Here, an α‐hemolysin nanopore, mass spectrometry (MS), and molecular dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Intermediate oligomeric states were previously detected in engineered helical peptides aggregating into quasiregular α-helical fibrils . Recent nanopore and mass spectrometry experiments also support the preference of lower-order and intermediate oligomers over higher-order oligomers for two other hLL-37 fragments, which explains the slow kinetics of octamer formation in our case …”
Section: Results and Discussionmentioning
confidence: 97%
“…Intermediate oligomeric states were previously detected in engineered helical peptides aggregating into quasiregular α-helical fibrils . Recent nanopore and mass spectrometry experiments also support the preference of lower-order and intermediate oligomers over higher-order oligomers for two other hLL-37 fragments, which explains the slow kinetics of octamer formation in our case …”
Section: Results and Discussionmentioning
confidence: 97%
“…The thin lipid film was added with pentane (99%, Sigma-Aldrich, Cat number: 236705) to a final concentration of 10 mg/mL. The lipid bilayer was formed followed by the Montal–Mueller technique. , Briefly, a homemade chamber separated by a 25 μm-thick Teflon film (Good Fellow Inc., #FP301200) with a 150 μm aperture was prepared. The aperture was pretreated by 0.5 μL of a 10% ( v / v ) hexadecane/pentane mixture and was dried immediately by N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, these NMR and DSC experimental results indicated that a toroidal pore-type membrane disruption is the likely possibility. Mechanisms of membrane interaction and disruption by LL-37 have also been investigated by other approaches [ 86 , 110 , 214 , 231 , 232 , 233 , 234 , 235 , 236 ].…”
Section: Solid-state Nmr Studies On the Mechanism Of Membrane Disrupt...mentioning
confidence: 99%
“…Taken together, these NMR and DSC experimental results indicated that a toroidal pore-type membrane disruption is the likely possibility. Mechanisms of membrane interaction and disruption by LL-37 have also been investigated by other approaches [86,110,214,[231][232][233][234][235][236]. To investigate the mechanism by which LL-37 perturbs the hydrophobic core of the lipid bilayer, a series of static 2H solid-state NMR and DSC experiments were carried out on lipid vesicles [237].…”
Section: Solid-state Nmr Studies On the Mechanism Of Membrane Disrupt...mentioning
confidence: 99%